Urinary Neutrophil Gelatinase-Associated Lipocalin (NGAL) Predicts Renal Function Decline in Patients With Glomerular Diseases - Coppolino, Giuseppe; Comi, Nicola; Bolignano, Davide; Patella, Gemma; Comi, Alessandro; Provenzano, Michele; Rivoli, Laura; Andreucci, Michele; Fuiano, Giorgio (Frontiers in Cell and Developmental Biology, 2020)
Objective: Available biomarkers for monitoring primary glomerulonephritides (GNs), often lack the ability to assess longitudinal changes and have great variability with poor sensitivity. Accruing evidence has demonstrated that Neutrophil Gelatinase-Associated Lipocalin (NGAL), holds promising capacities in predicting renal function worsening in various renal diseases. We aimed at analysing urinary NGAL (uNGAL) levels in a cohort of individuals with biopsy-proven GNs in order to evaluate its ability to reflect the entity of renal damage and to predict disease evolution overtime. Methods: We enrolled 61 consecutive GNs patients still naïve to pathogenic therapy. uNGAL levels were measured at baseline and patients prospectively followed until the manifestation of a combined outcome of doubling of baseline serum creatinine and/or end-stage kidney disease requiring permanent dialysis support. Results: Median uNGAL levels were 107 [35-312] ng/mL. At univariate and multivariate analyses an inverse correlation was found between eGFR and uNGAL levels (p=0.001). Progressor subjects showed exceedingly increased baseline uNGAL values as compared with non-progressors (p<0.001). Twenty-one patients (34%) reached the composite renal endpoint. Subjects with uNGAL values above the optimal, ROC-derived, cut-off of 107 ng/mL experienced a more rapid progression to the renal endpoint (p<0.001; HR: 5.47; 95% CI 2.31-12.95) with a mean follow-up time to progression of 73.4 vs. 83.5 months. Conclusions: In patients affected by primary glomerulonephritides, uNGAL may represent a real-time indicator of renal damage and an independent predictor of renal disease progression. Further studies on larger populations are warranted to confirm these findings.